1987
DOI: 10.1007/bf02057276
|View full text |Cite
|
Sign up to set email alerts
|

A role forAmanita muscaria L. in the circulation of cadmium and vanadium in a non-polluted woodland

Abstract: The sporophore of the fungusAmanita muscaria L. contains greatiy elevated levels of cadmium (29.9 μg g(-1) dwt) and vanadium (344.9 μg g(-1) dwt) in comparison with the soil in a birch woodland (total (HNO3-extractabie Cd 0.4 μg g(-1) dwt, V 11.7 μg g(-1) dwt). The significance of this remarkable concentration of normally rare and dispersed elements in terms of their circulation in the woodland has been investigated. Both elements are released from sporophore tissue in a form which can be taken up by a test pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Mushrooms can capture 137 Cs from the surface of soils and decaying litter and from deeper soil layers, and this is related to fungal biology and placement of mycelium and depth and structure of soil layers. Fungi certainly are involved in biogeocycling of 137 Cs and by decaying fruit bodies—like in the case of other mineral elements, fungus can recycle 137 Cs from deeper soil layers back to the surface of forest carpet (Lepp et al 1987; Smits and Hoffland 2009; Gryndler et al 2012). More or less severe cases of mushroom contamination with artificial radionuclides have been reported at sites or regions of nuclear weapons testing and nuclear power plant failure (Taira et al 2011).…”
Section: Radioactivity Of Mushroomsmentioning
confidence: 99%
“…Mushrooms can capture 137 Cs from the surface of soils and decaying litter and from deeper soil layers, and this is related to fungal biology and placement of mycelium and depth and structure of soil layers. Fungi certainly are involved in biogeocycling of 137 Cs and by decaying fruit bodies—like in the case of other mineral elements, fungus can recycle 137 Cs from deeper soil layers back to the surface of forest carpet (Lepp et al 1987; Smits and Hoffland 2009; Gryndler et al 2012). More or less severe cases of mushroom contamination with artificial radionuclides have been reported at sites or regions of nuclear weapons testing and nuclear power plant failure (Taira et al 2011).…”
Section: Radioactivity Of Mushroomsmentioning
confidence: 99%
“…Both extracellular and intracellular metal tolerance mechanisms have been described in mycorrhizal fungi, together with antioxidant defense systems aimed to counteract reactive oxygen species (ROS) directly or indirectly generated by metal ions (Bellion et al, 2006;Morel et al, 2008). Some mycorrhizal fungi have been shown to be capable of accumulating toxic metals such as Cd even in soils where these metals are only present in trace amounts (Berthelsen et al, 1995;Byrne et al, 1976;Lepp et al, 1987). Other studies have reported a reduced translocation of metal ions to the shoots of mycorrhized plants, leading, for example, to an increased tolerance toward zinc in Betula spp.…”
Section: Introductionmentioning
confidence: 99%
“…Fungi and including mushrooms take important role in metallic elements and metalloids turnover in the ecosystems (Lepp et al 1987;Falandysz and Borovička 2013). Numerous wild grown mushrooms are important as food resources to many local populations worldwide and they are also attractive and collected by fanciers and for commercial purchase in many countries (Aloupi et al 2011;Liu et al 2012;Nnorom et al 2012Nnorom et al , 2103Yağız et al 2008;Zhang et al 2008Zhang et al , 2010.…”
Section: Introductionmentioning
confidence: 99%